P142 Evaluating the vulval service within our genitourinary (GU) medicine department. (23rd May 2012) - Bradshaw, C; Patel, S; Dragovic, B
Abstract : Background: Vulval disorders with their psychosocial and psychosexual impact are frequently encountered within GU clinics. Dedicated specialist clinics should ideally be multidisciplinary with input from dermatology, GU and gynaecology; however this is not always feasible. A need for this service was recognised at our urban clinic—thus in 2005, a monthly vulval dermatoses clinic was set up and led by a GU physician with training in genital skin disease. In 2009 a monthly vulvodynia clinic was set up, staffed by a trained GU physician and psychosexual counsellor. Aims: To review our service provision over a 1-year period. Methods: Retrospective notes review of monthly vulval dermatoses and vulvodynia clinics were performed from November 2010–2011. Results: There were 145 vulval clinic appts; patients were only counted once—94 notes were reviewed. Vulval dermatoses clinic (n=40; 20 new, 20 f/u): median age 36 (IQR 29–44); referred by GUM 85%, derm/gynae 10%, GP 5%. Referral symptoms: itching (23), burning (8), dyspareunia (6), vulval pain (5), other (12); median length of symptoms 2 yrs (IQR 1–3). Predominant conditions were: psoriasis 28% (11) and lichen sclerosis 28% (11). Vulvodynia clinic (n=54; 24 new, 30 f/u): median age 28 (IQR 25–32); referred by GUM 67%, GP 26%, gynae/derm 7%. Referral symptoms: superficial dyspareunia (42), vulval pain (11), itching (2); median length of symptoms 2 yrs (IQR 1–5). Diagnosis of vulvodynia made in 74% (40/54). 22/40 were seen for f/u, 73% (16/22) reported at least 50% improvement in their symptoms with treatment. Conclusion: Our vulval service meets the needs of a significant number of symptomatic women allowing timely diagnosis, management and f/u. Recognising the multifactorial nature of vulval disorders means patients receive a thorough assessment in one clinic visit with a GU screen, dermatology review and psychosexual input, thus providing a service tailored to the patient.